High Intensity Focused Ultrasound Monitoring using Harmonic Motion Imaging for Focused Ultrasound (HMIFU) under boiling or slow denaturation conditions - Hou, Gary Y. (IEEE Trans Ultrason Ferroelectr Freq Control, 2015)
Harmonic Motion Imaging for Focused Ultrasound (HMIFU) is a recently developed High-Intensity Focused Ultrasound (HIFU) treatment monitoring method that utilizes an amplitude-modulated therapeutic ultrasound beam to induce an oscillatory radiation force at the HIFU focus and estimates the focal tissue displacement to monitor the HIFU thermal treatment. In this study, the performance of HMIFU under acoustic, thermal and mechanical effects were investigated. The performance of HMIFU was assessed in ex vivo canine liver specimens (n=13) under slow denaturation or boiling regimes. Passive Cavitation Detector (PCD) was used to assess the acoustic cavitation activity while a bare-wire thermocouple was used to monitor the focal temperature change. During lesioning with slow denaturation, high quality displacements (correlation coefficient above 0.97) were observed under minimum cavitation noise, indicating tissue the initial-softening-then-stiffening property change. During HIFU with boiling, HMIFU monitored a consistent change in lesion-to-background displacement contrast (0.46±0.37) despite the presence of strong cavitation noise due to boiling during lesion formation. Therefore, HMIFU effectively monitored softening-then-stiffening during lesioning under slow denaturation, and detected lesioning under boiling with a distinct change in displacement contrast under boiling in the presence of cavitation. In conclusion, HMIFU was shown effective in HIFU monitoring and lesioning identification without being significantly affected by cavitation noise.